Valuation of forest carbon stocks to estimate the potential for result-based payment under REDD+ in Cameroon - Sonwa, D.J.; Nlom, J.H.; Neba, G. (Commonwealth Forestry Association, 2016)
This study base on existing scientific literature makes an economic evaluation of carbon stocks gained under different deforestation and forest degradation scenarios (100, 50 and 25% avoided deforestation) during a 20 years period (2010–2030). It analyzes the associated financial commitments to achieve greenhouse gas emission reduction, and further discusses deforestation avoidance in the context of the 2035 emergence ambition of Cameroon. The Cumulative Stock of carbon potentially avoided during the period 2010–2030 for the 3 scenarios are 151.10 Mt, 75.55 Mt and 37.77 Mt respectively for 100%, 50% and 25% avoided deforestation. This can lead to an anticipated cumulative carbon revenue of 1 670 648 017. 37 US$; 835 324 008. 69 US$; and 417 662 004. 34 US$ respectively for the 3 deforestation scenarios. Other services such as biodiversity are discussed as co-benefits that can be derived from forest management. The current study thus provides basic information which can help to enrich the debate on the feasibility of REDD+ implementation in Cameroon.